بناء مقياس الانهزام النفسي لدى طلبة الصف الرابع لبعض كليات التربية الرياضية في اقليم كوردستان - منصور, حازم علوان; كريم, فرهاد ابراهيم (Sulaimani Journal for Humanities, 2021)
This study aimed to develop a psychological self-defeatism scale in fourth stage students of some physical education colleges in Kurdistan region. The researchers used descriptive survey research design. The research sample consisted of (337) fourth-stage students of some physical education colleges in Koya University, University of Sulaimani and Salahaddin University in Kurdistan Region. The construction procedure of the scale was pointing a definition of psychological self- defeatism where the researchers relied on the behavioral school in defining psychological self-defeatism and the findings of the French psychological scientist (John Broadus Watson ) when his theory focused on defining behavior according to its relationship and correlation with psychology depending on the basics and principles of the theory, including repeating of behavior and past experiences, especially concentrating on motivation, whether it is an external or internal, and the desire to satisfy the needs to reach satisfaction in all domains and to stay away from the sources of psychological self-defeatism. Accordingly, the psychological self-defeatism was defined, and then the scale domains were determined which consists of (5) domains, as a part of the followed definition, with a definition of each domains of the scale in order to collect and draft the scale sections and the sections of each domains were drafted in their initial form. As it was possible to collect (60) sections through research and review of previous studies on the concept of psychological self-defeatism in general and then transformed into psychological self-defeatism in sports field. As well as adopting the scientific steps and procedures in developing the scale including discriminatory power, scientific basis and standard error. psychological self-defeatism in sports field: it is a state of collapse of students' psychological resistance, inability feeling, helplessness, and lack of personal effectiveness, which faces physical educations fourth-stage students as a result of Frustration, despair and pessimist in terms of understanding the study materials from the cognitive and practical aspects which makes him/her devastated in terms of psychological, emotional, social, intellectual and economical aspects. Procedural definition of psychological self-defeatism: It is the total score obtained by fourth-stage students of some physical education colleges in Kurdistan region in light of their response to the sections of the psychological self-defeatism scale, which the researchers developed within the limits of the current research sample. The scale consists of five domains which are (sport psychology, social sport, sport safety, sport economy and sport education) domains.
Keywords: psychological selfdefeatism scale; fourthstage students of some physical education colleges